Skin microvascular function and renal hemodynamics in overweight patients with type 2 diabetes: A cross‐sectional study. (6th May 2021) - Bouman, Emma J.; Smits, Mark M.; van Bommel, Erik J.; Muskiet, Marcel H. A.; Hesp, Anne C.; Serné, Erik H.; Joles, Jaap A.; van Raalte, Daniël H.
Abstract: Objective: Diabetic kidney disease is a microvascular complication of diabetes. Here, we assessed the association between skin microvascular function and renal hemodynamic function in a cohort of well‐phenotyped adults with type 2 diabetes (T2D). Methods: We included 81 overweight/obese adults (age: 62 ± 8 years; BMI: 32 ± 4 kg/m 2 ) with well‐controlled T2D and no renal impairment. Skin microvascular function was assessed by nailfold capillary density in rest and after arterial occlusion (ie, peak capillary density). Renal hemodynamic functions (ie, measured glomerular filtration rate [mGFR], effective renal blood flow [ERBF], filtration fraction [FF], and effective renal vascular resistance [ERVR]) were assessed by combined inulin and para‐aminohippurate clearances and blood pressure measurements. Results: Skin capillary density was 45 ± 10 capillaries/mm 2 at baseline and 57 ± 11 capillaries/mm 2 during post‐occlusive peak; mGFR averaged 108 ± 20 ml/min. In multivariable regression analyses, positive associations between capillary density during post‐occlusive peak and mGFR ( β = 0.224; p = 0.022) and ERBF ( β = 0.203; p = 0.020) and a positive trend for hyperemia and mGFR ( β = 0.391; p = 0.053) were observed, while a negative association for post‐occlusive capillary density with ERVR (β = −0.196; p = 0.027) was found. Conclusion: These findings indicate that microvascular dysfunction in overweight adults with T2D is associated with lower mGFR and ERPF and higher ERVR. We hypothesize that increased renal vascular resistance may contribute to glomerular dysfunction due to impaired renal perfusion.